(untitled) (Bangladesh Journal of Zoology, 2015)
Prevalence of five important blood transfusion-transmitted infectious diseases (HIV, HBV, HCV, Syphilis, and Malaria) were studied among the voluntary blood donors in Dhaka. Out of 1500 donors, positive infections was identified in 99 of cases and rest of the donors were screened negative. Male voluntary blood donor were 82% and only 18% were female. About 53.53% male infectious blood donor had HBV infection whereas, 26.26% female had HBV. The difference was significant (P < 0.05). In age group of 18-24 years, 36% of the donor had HBV infection and HCV was found positive in 04.04% of student. Among the students, HBV was positive in 44%. Only 01.01% of teacher was HIV positive. Malaria infection was positive only among the business man (01.01%). The positive cases (01.01%) with TPHA found among the students, teacher and worker and the difference was significant (P<0.05). 40.40% of the volunteer blood donors were illiterate and 24.24% donor had Master degree and 8% HSC passed. Bangladesh J. Zool. 42(1): 77-84, 2014